Factors For Cessations of Exclusive Breast Feeding at End Of 6 Weeks in Healthy Term and Late Preterm Neonates Born in A Hospital Set Up in North India - Jain, Suksham; Singla , Manju; Chawla , Deepak (National Journal of Community Medicine, 2012)
Background: Millions of deaths can be averted by scaling up exclusive breast feeding, EBF rate. By end of 2 months only 69% of mothers and by 4-6 months only one quarter of mothers are giving EBF to their babies. Factors influencing non-initiation or early cessation of exclusive breastfeeding had already been evaluated under NFHS data but only for babies born in community settings, these factors need to be investigated for the neonates born out of community settings. Objectives: To identify risk factors for early cessation of exclusive breast-feeding. Setting: Teaching Hospital in north India. Subjects: Mothers giving birth to term or late pre-term healthy neonates were enrolled within 48 h after delivery and followed up till 6th postnatal week. Results: A total of 350 mothers were enrolled. At the end of 1st, 2nd and 6th week the proportion of EBF decreased to 95%, 93.3% and 75.8% respectively. Risk factors associated with early cessation of exclusive breastfeeding were cesarean section at end of six weeks was primiparous mothers (RR: 1.95, 95%CI: 1.01-3.79). Conclusion: First time mothers need more counseling on exclusive breast-feeding.